Slopovers : fire surveys of the mid-American oak woodlands, Pacific Northwest, and Alaska - Pyne, Stephen J., 1949- (Pyne, Stephen J., 1949- To the last smoke, 2019)
America is not simply a federation of states but a confederation of regions. Some have always held national attention, some just for a time. Slopovers examines three regions that once dominated the national narrative and may now be returning to prominence. The Mid-American oak woodlands were the scene of vigorous settlement in the late eighteenth and early nineteenth centuries and thus the scene of changing fire practices. The debate over the origin of the prairies--by climate or fire--foreshadowed the more recent debate about fire in oak and hickory hardwoods. In both cases, today's thinking points to the critical role of fire. The Pacific Northwest was the great pivot between laissez-faire logging and state-sponsored conservation and the fires that would accompany each. Then fire faded as an environmental issue. But it has returned over the past decade like an avenging angel, forcing the region to again consider the defining dialectic between axe and flame. And Alaska--Alaska is different, as everyone says. It came late to wildland fire protection, then managed an extraordinary transfiguration into the most successful American region to restore something like the historic fire regime. But Alaska is also a petrostate, and climate change may be making it the vanguard of what the Anthropocene will mean for American fire overall. Slopovers collates surveys of these three regions into the national narrative. With a unique mixture of journalism, history, and literary imagination, renowned fire expert Stephen J. Pyne shows how culture and nature, fire from nature and fire from people, interact to shape our world with three case studies in public policy and the challenging questions they pose about the future we will share with fire.